The Effectivenes Of Using Flash Cards To Teach Students' Vocabulary Mastery At SMP Darut Tauhid - Nursih, Nursih; Nizarrahmadi, Nizarrahmadi; Yassin, Muhammad (JURNAL JENDELA PENDIDIKAN, 2024)
Vocabulary is an essential element of language ability and serves as a foundation for pupils' speaking, listening, reading, and writing abilities.This study aims to determine the effectivenes of using flash cards to teach students’ vocabulary mastery at SMP Darut Tauhid. The research design is independent sample t-test, while the research method is quantitative. The participants in this study all student`classVII totaling 60 people, 30 male students and 30 female students. the data in this study were collected using instruments pre-test and posh-test (multiple choice), then normality test, homogeneity test and descriptive statistics were used to evaluate data analysis requirements. in this study the independent sample t test analysis was used to test the hypothesis using computer software assistance through the SPSS (Statistcal Package For the Scial Sciens) version 25 for windows program. Based on the results of research and discussion, the following conclusions can be drawn: There is an effectivenes of using flash cards to teach students’ vocabulary mastery at SMP Darut Tauhid. This is indicated by the results of the significance (2-tailed) of 0.000 < 0.05 then as the basis for the performance of the decision in the independent sample test, it can be concluded that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is The use of Flash cards effective on students‟ vocabulary at SMP Darut Tauhid.